Vicuñas (Vicugna vicugna), Wild Andean Altiplano Camelids: Multiple Valuation for Their Sustainable Use and Biocultural Role in Local Communities - Vila, Bibiana Leonor (2021)
In these case studies, vicuñas are presented as biocultural components of the Andean altiplano's socioecological landscape. The environmental history of vicuñas is related to the multiple values of the species, especially of its appreciated fiber as a nature contribution to people. Vicuñas were in risk of extinction, but thanks to conservation policies, the engagement of local communities, and the efforts of scientists and naturalists, this species has recovered to an extent than allows sustainable, community-based management via chakus, a traditional method involving the capture and release of wild vicuñas to harvest their fiber. We describe two cases where the VICAM research team (former MACS) was summoned by local institutions in Cieneguillas and Santa Catalina, both localities belonging to the Pozuelos UNESCO MAB Biosphere Reserve in Jujuy, Argentina. The process to launch and maintain the sustainable use of vicuñas is presented, focusing on the emerging challenges, dilemmas, and conflicts that shaped decision-making processes. The obstacle that seemed the most challenging beforehand? the capture itself and its biological consequences for the animals? was overcome with the development of adaptive management. Vicuña management has great potential for the sustainable development of indigenous peoples and local communities, but achieving this goal is a process ridden with difficulties, including the commercial interests of non-Andean actors. For vicuña management to become a driver of sustainable local development, a series of challenges must be overcome: power asymmetries between local communities and other stakeholders due to the monistic economic valuation of vicuña fiber, the incorporation of relational values with strict welfare protocols recognizing vicuñas as sentient beings, and the intrinsic valuation of the ecological role of the species, also considering their indisputable position as Andean ancestral biocultural heritage.